A critical discourse analysis of the New Labour discourse of Social and Emotional Learning (SEL) across schools in England and Wales: Conversations with policymakers - Carl Emery (Arizona State University, 2016)
This paper reports on a critical discourse analysis (CDA) of the New Labour (1997-2010) discourse of Social and Emotional Learning (SEL) in schools, and how it was understood and enacted by policymakers in England and in Wales within the context of devolved government across the UK. By SEL I mean universal school-based programs, located in the concept of children's emotional wellbeing and concerned with developing children's ability to understand, express and manage their emotions. Through a series of in-depth interviews with national level SEL policy actors this investigation worked to understand and identify how the SEL policy discourse worked "to privilege certain ideas and topics and speakers and exclude others" (Ball, 2008, p. 5). Through shining a critical light on the discourse of New Labour SEL policy makers this work responds to the call of Gunter et al. (2014) for critical education researchers to develop and amplify voices which challenge the current hegemonic "common sense" discourse. The findings identify that the relationship between language and political ideology in England and Wales during the New Labour years powerfully shaped the SEL policy discourse.